Implementation of Pancasila Economic System Based on Sustainable Development Based on Kinship - Harefa, Amstrong; Harefa, Jesslyn Elisandra (Sahabat Publikasi, 2024)
The Pancasila economic system aims to renew the national economy in a structured, systematic, and massive manner by ensuring constitutional freedom in sustainable development based on family values to improve the quality of human life. The research formulates an effective strategy to implement the Pancasila Economic System within sustainable development, identifying challenges and obstacles and evaluating the impact of its family-based approach. This study employs literature research, collecting data through reviews of books, articles, journals, and relevant internet sources. The data collection tool is document research, and the data is analyzed qualitatively. Results indicate that an effective strategy for implementing the Pancasila economic system involves stakeholder and government involvement in policy-making, using a conceptual foundation to guide development. The system faces challenges such as global competition, foreign cultural influences, and technological transformation. To address these, collaboration among the government, private sector, and community is essential. For economic progress, the Pancasila economic democracy should be implemented based on kinship principles, emphasizing ethical, democratic values and a social sense of kinship among economic actors.